PENGARUH WORK LIFE BALANCE DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN MILENIAL DENGAN STRES KERJA SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PT XYZ) - Sharfina Ferzanita (2023)
The purpose of this study is to determine and prove the influence of work-life balance on turnover intention, to determine and prove the influence of compensation on turnover intention, to determine and prove the influence of work- life balance on turnover intention mediated by jobstress, to determine and prove the influence of compensation on turnover intention mediated by jobstress, and to determine and prove the influence of jobstress on turnover intention. A quantitative approach was used in this study with a total sample of 32 employees of PT XYZ using census sampling method. This study used SmartPLS 3.0 as a tool for data analyzing with The Structural Equation Model (SEM) based on Partial Least Square (PLS). The results of this study found that (1) work-life balance has a positive and significant effect on turnover intention, (2) compensation has no effect and is not significant on turnover intention, (3) work-life balance has a positive and significant effect on turnover intention mediated by jobstress, (4) compensation has a positive and significant effect on turnover intention mediated by jobstress, and (5) jobstress has a positive and significant effect on turnover intention.